2018
DOI: 10.3390/v10060283
|View full text |Cite
|
Sign up to set email alerts
|

Saracatinib Inhibits Middle East Respiratory Syndrome-Coronavirus Replication In Vitro

Abstract: The Middle East respiratory syndrome-coronavirus (MERS-CoV), first identified in Saudi Arabia, is an emerging zoonotic pathogen that causes severe acute respiratory illness in humans with a high fatality rate. Since its emergence, MERS-CoV continues to spread to countries outside of the Arabian Peninsula and gives rise to sporadic human infections following the entry of infected individuals to other countries, which can precipitate outbreaks similar to the one that occurred in South Korea in 2015. Current ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 55 publications
(122 reference statements)
0
93
0
1
Order By: Relevance
“…Moreover, the combination of INF-α2b and ribavirin in Vero cells showed augmentation of action and facilitates the reduction of the doses of IFN-α2b and ribavirin to lower concentrations suggesting possible utility in clinical use [30]. Saracatinib with Gemcitabine had no difference in cytotoxicity compared with Saracatinib alone but was less cytotoxic compared with gemcitabine alone [44]. There were many drugs that were used in vitro and showed effectiveness, however, translating the findings from these studies into clinical trial remains of particular importance especially taking into consideration availability, pharmacokinetic properties, pharmacodynamic characteristics and possible side effects [69].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the combination of INF-α2b and ribavirin in Vero cells showed augmentation of action and facilitates the reduction of the doses of IFN-α2b and ribavirin to lower concentrations suggesting possible utility in clinical use [30]. Saracatinib with Gemcitabine had no difference in cytotoxicity compared with Saracatinib alone but was less cytotoxic compared with gemcitabine alone [44]. There were many drugs that were used in vitro and showed effectiveness, however, translating the findings from these studies into clinical trial remains of particular importance especially taking into consideration availability, pharmacokinetic properties, pharmacodynamic characteristics and possible side effects [69].…”
Section: Discussionmentioning
confidence: 99%
“…Saracatinib has a broad-spectrum antiviral activity against different strain of MERS-CoV. After 72 h of infection of Huh-7 cells, Saracatinib exhibited an EC50 of 2.9 μM and CC50 of more than 50 μM [44]. Whereas, gemcitabine was shown to be effective against MERS-CoV infected Huh-7 cells with an EC50 of 1.2 μM and a complete viral depletion at a dose of ≥1 μM [44].…”
Section: In Vitro Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Current anti-MERS-CoV agents have been primarily resulted from previous drugs used for the SARS-CoV infection. To identify potential antiviral agents against MERS-CoV, Shin et al screened a library consisting of 2334 approved drugs and pharmaceutically active compounds [76]. This yielded a series of hit compounds, primarily categorized as anti-protozoal, anti-cancer, anti-psychotics (11-18, Fig.…”
Section: Approaches For the Development Of Anti-viral Drugsmentioning
confidence: 99%
“…The co-crystal structures of SARS-CoV 3CL pro with decahydroisoquinoline inhibitors (76)(77)(78)(79)(80) revealed that P2-decahydroisoquinoline scaffold was inserted into a large S2 pocket and the P1-imidazole was occupied into the S1 pocket as Structure of 3CL pro inhibitors that contain Michael acceptor, aldehyde and activated carbonyl functional groups.…”
Section: Mers-cov and Sars-cov Pl Proteases Inhibitorsmentioning
confidence: 99%